2019
DOI: 10.1155/2019/7276389
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of Collagen Gene Family in the Brain Regions of Male Mice with Behavioral Psychopathologies Induced by Chronic Agonistic Interactions

Abstract: Chronic agonistic interactions promote the development of experimental psychopathologies in animals: a depression-like state in chronically defeated mice and the pathology of aggressive behavior in the mice with repeated wins. The abundant research data indicate that such psychopathological states are associated with significant molecular and cellular changes in the brain. This paper aims to study the influence of a 20-day period of agonistic interactions on the expression patterns of collagen family genes enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 74 publications
1
8
0
1
Order By: Relevance
“…We have previously found downregulation of collagen genes encoding proteins that are the main components of the extracellular matrix in the ventral segmental areas of male mice with repeated experiences of aggression [77]. These data, together with decreased expression of Slc * genes, support the view that neural plasticity accompanied by a decreased synaptic connections in brain regions that are involved in neuropsychiatric disorders, may be reduced.…”
Section: Discussionsupporting
confidence: 56%
“…We have previously found downregulation of collagen genes encoding proteins that are the main components of the extracellular matrix in the ventral segmental areas of male mice with repeated experiences of aggression [77]. These data, together with decreased expression of Slc * genes, support the view that neural plasticity accompanied by a decreased synaptic connections in brain regions that are involved in neuropsychiatric disorders, may be reduced.…”
Section: Discussionsupporting
confidence: 56%
“…In previous publications of our group, it was shown that stress resulting from daily agonistic interactions causes crucial changes in the expression of many genes in various brain regions of adult mice [ 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Earlier, we described in detail changes in the transcription of the genes associated with the neurotransmitter systems functioning in the ventral tegmental area (VTA) of defeated male mice as compared to the controls that did not have an agonistic interaction experience [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it's necessary to take into consideration that numerous genes associated both with lithium exposure and bipolar disorder were also identified [36][37][38][39]41], and differential expression of these genes in brain tissue samples from patients and healthy controls was studied [63]: lithium exposure significantly affected 1108 genes, 702 of which were upregulated and 406 genes were downregulated. Our neurogenomic data, obtained in last years by whole transcriptomic analysis, [72,73] and collagen [74] genes specific for brain regions in mice with mixed anxiety/depression-like state. It confirms that there are many mechanisms that may account for the effects of lithium [39,75,76] on the neurochemical, cellular, and genomic levels.…”
Section: Resultsmentioning
confidence: 99%
“…However, it's necessary to take into consideration that numerous genes associated both with lithium exposure and bipolar disorder were also identified [36][37][38][39]41], and differential expression of these genes in brain tissue samples from patients and healthy controls was studied [63]: lithium exposure significantly affected 1108 genes, 702 of which were upregulated and 406 genes were downregulated. Our neurogenomic data, obtained in last years by whole transcriptomic analysis, revealed changes in the expression of mitochondrial [64], ribosomal [65,66], monoaminergic [67][68][69][70], autistic [71] genes as well as changes in the expression of neurotrophic, transcription factors [72,73] and collagen [74]…”
Section: Resultsmentioning
confidence: 99%